Characterization of Extra- and Intracellular Phytases from Bacteria Proliferating during Tempe Production - Sutardi Sutardi (Indonesian Association of Food Technologists, 2003)
Bacteria species Streptococcus faecium and Streptococcus dysgalactiae, proliferating during tempe (fermented soybeans) production produced both extra- and intracellular phytases. The enzymes were isolated from growth media and the cultured bacteria and partially purified by acetone fractionation. Extracellular phytase activities were higher than that of the intracellular enzymes. The extra- and intracellular phytases of S. faecium and S. dysgalactiae acted over a nerrow pH range at 4.1 – 4.3 and the maximum activity at 45